Electrostatic potential and trajectory of an electron in single electron transistor - Ithnin, Hanafi (2012)
Tunneling of an electron from the electrode towards the island in single electron transistor (SET) is a quantum mechanical phenomenon. This means, that electron can either tunnels to the island or not depending on the probability. Therefore, the study on how the electron interacts with a quantum dot should give the needed information in advancing the development of SET. With several assumptions, the electron trajectory from the electrode towards the island is studied in this research using classical approaches. The island is first developed by optimizing gallium arsenide (GaAs) cluster using the parallel version of GAMESS package. With the information from the optimized cluster, GaAs quantum dot is built as an island for the SET. The dot has a square bipyramidal shape with total 84 atoms in 1.6 nm3 volume. Then the external electric field is applied towards the dot to study the potential distribution in the vicinity of the dot. Using this potential distribution, the electron trajectory is mapped and plotted using MacMolPlt and GnuPlot programs. The plotted result shows how the electron moves towards the dot and sticks in a loop. It is found that the loop is caused by the attraction of atomic nucleus of one of the atom in the dot. As the conclusion, the electron trajectory is discovered and plotted from the source electrode to the island. On the other hand, the electron does not pass through the island to the drain because of nuclear attraction which can be improved in future simulation.